Genotype-Environmental (G x E) Interaction for Body Weights for Kuchi Chicken Ecotype of Tanzania Reared On-Station and On-Farm - Lwelamira , J. (International Journal of Poultry Science, 2012)
This study was carried out with the aim of determining magnitude of G x E interaction for body weights for Kuchi chicken ecotype of Tanzania reared under intensive (on-station) and extensive (free-range) management systems. Body weight was assessed at 8 (Bwt8), 12 (Bwt12), 16 (Bwt16) and 20 (Bwt20) weeks of age. Results for this study indicated average performance in all body weight measurements was significantly higher under intensive management compared to extensive management (p<0.001), signifying two diverse environment and hence possibility for G x E interaction. Results of this study further indicated that there was significant Sire-Environment (S x E) interaction (p<0.001) for all body weight measurements which led to Genotype-Environment interaction for these traits. Based on magnitude of genetic correlation for the same trait measured in two environments rg, G x E interaction for all body weight measurements were found to be biologically important (substantial). Value for rg was 0.745, 0.757, 0.752 and 0.753 for Bwt8, Bwt12, Bwt16 and Bwt20, respectively. Since breeding program for improving performance of the ecotype would be more feasible under intensive management and hence more likely to take place under such environment, based on results of this study, if such breeding program is to be implemented, sensitization of smallholder farmers (beneficiaries of the breeding program) to shift from their current system of management (extensive management) to at least semi-intensive system of management is recommended for minimizing the effect of G x E interaction.